Hubungan Usia dan Tingkat Pendidikan dengan Tingkat Kecemasan Pra Operasi pada Pasien Kanker Payudara di RSUD Abdoel Wahab Sjahranie Samarinda: The Relationship between Age and Education Level with Pre-operative Anxiety Level in Breast Cancer Patients at RSUD Abdoel Wahab Sjahranie Samarinda - Bidadari, Titis Mukti; Rachmi, Eva; Ramadhanny, Candra (ITKES Wiyata Husada Samarinda, 2024)
ABSTRACT Anxiety was the highest mental disorder in the world in 2019. In Indonesia, anxiety increased by 9.8% in 2018. Pre-operative anxiety is often found in breast cancer patients, among other things, induced by primary therapy in the form of surgery. Pre-operative anxiety can lead to postponement and cancellation of surgery. Previous research shows that age and education are two factors whose influence on anxiety shows inconsistent results. This study aims to determine the relationship between age and education level with pre-operative anxiety levels in breast cancer patients at Abdoel Wahab Sjahranie Hospital, Samarinda. This research uses an observational analytical design with a cross sectional approach. Sampling was carried out using the consecutive sampling method and involved 30 patients who met the research criteria. The patient's anxiety level is measured using the Beck Anxiety Inventory (BAI) questionnaire. Bivariate test data were analyzed using the Chi-Square test. The results showed that the majority of respondents belonged to the adult age category (53.3%), the majority of respondents had primary and secondary education levels (40% each), the relationship between age and pre-operative anxiety levels in breast cancer patients at Abdoel Wahab Sjahranie Hospital Samarinda not significant (p-value = 0.153), and the relationship between education level and pre-operative anxiety level in patients with breast cancer at Abdoel Wahab Sjahranie Samarinda Hospital was significant (p-value = 0.004). Pre-operative anxiety in breast cancer patients at Abdoel Wahab Sjahranie Hospital Samarinda is related to the patient's education level but is not related to the patient's age.